Reliability analysis of underground tunnel: an overview - Thapa, Axay; Roy, Atin; Chakraborty, Subrata (Journal of Structural Engineering, 2024)
Probabilistic analysis of underground tunnels is getting increasing importance as the approach can explicitly consider inherent uncertainties in the involved parameters to provide a rational perspective in the analysis and design of underground tunnel structures. In fact, reliability analysis of underground tunnels is an active field of research in recent years. Like reliability analysis of any other structure, the developments in tunnel reliability analysis approaches have also taken place under two sub-heads i.e. analytical and simulation-based approaches. Noting the difficulty of performing reliability analysis by those approaches for real-life tunnels that involves evaluation of implicit nonlinear performance functions by tiring finite element simulation, the metamodel-based reliability analysis approach has been widely applied in tunnel reliability analysis. The present article provides an overview of related developments in analytical and simulation-based tunnel reliability analysis with special emphasis on the application of various metamodeling approaches in such analysis. Based on the overview of the developments in tunnel reliability analysis presented here, the challenges and opportunities in the field are summarized. The article is likely to augment the stateof- the-art developments of tunnel reliability analysis.